A contribution to the theory of fertility and economic development - Luca Gori; Mauro Sodini (Global Labor Organization (GLO), 2018)
The aim of this research is to build on a theory for explaining economic development in a (neoclassical) growth model with endogenous fertility. The economy is comprised of overlapping generations of rational and identical individuals and identical competitive firms producing with a constant-returns-to-scale technology with no externalities. From a theoretical perspective, the distinguishing feature of this work is that endogenous fertility per se is able to explain the existence of low and high development regimes. It provides alternative reasons (history driven or expectations driven) why some countries enter development trajectories with high GDP and low fertility and others experience under-performances with low GDP and high fertility. The model is also able to reproduce fertility fluctuations and explain the baby busts and baby booms observed in the last century in some developed countries.
Keywords: C61; C62; J1; J22; O41; 330; Economic development; Endogenous fertility; Local and global indeterminacy; OLG model